2021
DOI: 10.3389/fmicb.2021.626421
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of the Microbiota in the Full-Term Fetal Gut and Amniotic Fluid: A Bovine Cesarean Section Study

Abstract: The development of a healthy intestinal immune system requires early microbial exposure. However, it remains unclear whether microbial exposure already begins at the prenatal stage. Analysis of such low microbial biomass environments are challenging due to contamination issues. The aims of the current study were to assess the bacterial load and characterize the bacterial composition of the amniotic fluid and meconium of full-term calves, leading to a better knowledge of prenatal bacterial seeding of the fetal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 63 publications
9
50
0
Order By: Relevance
“…The fetal bacterial microbiota was dominated by the Proteobacteria, Firmicutes, Actinobacteriota and Bacteroidota phyla. Similar to our study, previous studies reported the presence of an archaeal and bacterial microbiota in amniotic fluid and the intestine of 5-, 6-and 7month-old fetuses (Angus × Friesian bred) (Guzman et al, 2020), and C-section derived near fullterm calf fetuses (Belgian Blue) (Husso et al, 2021). The dominant bacterial phyla observed in the 83-day-old fetuses in the present study were also the predominant phyla in these mid-and fullterm calf fetuses and in the calves postnatally.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The fetal bacterial microbiota was dominated by the Proteobacteria, Firmicutes, Actinobacteriota and Bacteroidota phyla. Similar to our study, previous studies reported the presence of an archaeal and bacterial microbiota in amniotic fluid and the intestine of 5-, 6-and 7month-old fetuses (Angus × Friesian bred) (Guzman et al, 2020), and C-section derived near fullterm calf fetuses (Belgian Blue) (Husso et al, 2021). The dominant bacterial phyla observed in the 83-day-old fetuses in the present study were also the predominant phyla in these mid-and fullterm calf fetuses and in the calves postnatally.…”
Section: Discussionsupporting
confidence: 91%
“…However, this was challenged by recent evidence showing that prenatal microbial colonization may take place in the intestine of fetal calves. Results of a bovine caesarean section study that was conducted to evaluate bacterial load and the bacterial composition of the amniotic fluid and meconium of near full-term calves using 16S rRNA gene sequencing, qPCR and culturing suggested that in utero maternal-fetal bacterial transmission may occur before birth in calves (Husso et al, 2021). In addition, Guzman et al, (2020) investigated the presence of a microbiota in amniotic fluid and in 5 sample types from the gastrointestinal tract (GIT) of 5-, 6-and 7-monthold calf fetuses using both molecular and culture-based approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, bacteria were found in fetal membranes and umbilical cords but never inside the placenta, supporting the hypothesis of contamination as the source of bacterial presence in studies that challenge the "sterile womb" hypothesis [15]. As for the amniotic fluid, a recent study in a bovine C-section model revealed some positives (5 out of 24), with low amounts of bacteria in the meconium, but none of the amniotic fluid samples presented different amounts of bacterial DNA compared to the negative controls [16]. In a recent study, fecal meconium was collected before antibiotic administration during breech CSDs without labor and compared to standard VDs, first-pass meconium, and stool.…”
Section: Introductionmentioning
confidence: 63%
“…Maternal genetics ( Goodrich et al, 2014 ), gene mutation ( Strati et al, 2016 ), delivery methods ( Bi et al, 2021 ; Husso et al, 2021 ), age ( Yatsunenko et al, 2012 ), disease ( Alkanani et al, 2015 ), diet ( David et al, 2014 ; Angoa-Pérez et al, 2020 ), and medication ( Forslund et al, 2013 ) are the dominant factors in shaping the composition and abundance of intestinal microbiota. It is reported that the composition of intestinal bacterial communities in human and other mammals after suckling is mainly dominated by the phyla Firmicutes and Bacteroidetes, followed by the phyla Proteobacteria, Actinobacteria, and Verrucomicrobia ( Gill et al, 2006 ; Duncan et al, 2008 ; Ley et al, 2008 ); however, the compositions of bacteria in the meconium of fetal bovine and lamb delivered by cesarean section were primarily composed of the phyla Proteobacteria and Firmicutes instead of Firmicutes and Bacteroidetes ( Bi et al, 2021 ; Husso et al, 2021 ), and data in our study also indicated that Firmicutes and Proteobacteria were the most abundant phyla in the meconium of vaginal-delivered neonatal piglets before suckling.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota is integral to feed digestion, nutrient absorption and metabolism, immune response, and gastrointestinal development ( Morgavi et al, 2015 ), and the colonization of intestinal microbiota during early life could further influence the subsequent microbiota of adult host ( Ben Salem et al, 2005 ). Many studies demonstrated that the intestine of prenatal animals really has microorganism ( Alipour et al, 2018 ; Stinson et al, 2019 ; Hummel et al, 2020 ; Bi et al, 2021 ; Husso et al, 2021 ), and at present, no literature on the differences in intestinal microbiota composition between mutant and wild-type fetuses is found, but for postnatal individuals, there are differences in gut microbiota between mutant and wild-type host, for example, nucleotide-binding oligomerization domain-containing protein 2 (NOD2) mutation caused Crohn’s disease (CD) ( Hampe et al, 2001 ; Ogura et al, 2001 ) and Crohn’s disease individuals had lower bacterial diversity than healthy controls ( Joossens et al, 2011 ). Cystic fibrosis transmembrane conductance regulator (CFTR) mutation resulted in multiorgan defects, and CFTR –/– mice had significantly lower alpha diversity of intestinal bacterial community ( p < 0.05) and had reduced relative abundance of protective species such as Acinetobacter lwoffii and Lactobacilliales members compared with wild-type mice ( Lynch et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%